El papel de un Banco Central sin responsabilidades de políticas monetarias - Sterlepper, Jurgen (2003)
At first glance, a Central Bank with no monetary policy responsibilities would seem a bit strange. You can think of images of a bird without wings or a shark without teeth. Certainly, this is a situation in which the Central Banks could not be happy; however, this is by no means a catastrophe, as central banks still play a range of roles in the economy, even without having monetary policy responsibilities. By monetary policy we understand all the measures that the Central Bank can take to influence the international and national stability of its own currency. I have used internationally the verb "influence" and not the verb "direct"